Effects of vagus nerve stimulation on cognitive function in patients with epilepsy: a systematic review and meta-analysis - Kong, Yurou; Zhao, Kun; Zeng, Duchun; Lu, Feiao; Li, Xiang; Wu, Yulun; Jiang, Zengming; Wen, Wanshun (Frontiers in Neurology, 2024)
Background: Previous studies showed that vagus nerve stimulation (VNS) can improve cognitive function in patients with epilepsy, but there is still great controversy about the effect of VNS on cognitive function in patients with epilepsy. Objective: To investigate the effect of VNS on the cognitive function of epilepsy patients. Methods: Clinical trials published in PubMed, The Cochrane Library, and Embase before September 20, 2022, were comprehensively searched. Primary outcomes were overall cognitive performance, executive function, attention, memory; Secondary outcomes were seizure frequency, mood, and quality of life (QOL). Random effects were used to calculate the pooled outcome. Results: Twenty clinical trials were included. There was no significant improvement in overall cognitive performance in patients with epilepsy after VNS treatment (SMD = 0.07; 95% CI: -0.12 to 0.26; I2=0.00%) compared to pre-treatment. Compared to pre-treatment, there was no significant difference in executive function (SMD = -0.50; 95% CI: -1.50 to 0.50; P = 0.32), attention (SMD = -0.17; 95% CI: -0.43 to 0.09; P = 0.21) and memory (SMD = 0.64; 95% CI: -0.11 to 1.39; P = 0.09), but there were significant differences in seizure frequency, mood, and quality of life in patients with epilepsy after VNS. Conclusions: This meta-analysis did not establish that VNS can significantly improve cognitive function in patients with epilepsy, but it shows that VNS can significantly improve the seizure frequency, mood and quality of life of patients with epilepsy.